Economic Ways to Improve the Mechanization of Production - RUSNAK, Alla V.; BUZHYMSKA, Kateryna A.; TKACHUK, Hanna Yu.; PAVLOVA, Svitlana I.; OVANDER, Nataliia L. (Journal of Advanced Research in Law and Economics, 2018)
The relevance of the work is determined by the fact that the issues of improving production capacity and mechanization of an enterprise are determined in a modern globalized economy as the ability of enterprises to maintain competitiveness through economic improvement of production processes. In the article, the authors equate the term mechanization with the increase or retention of the modern level of technical equipment of the enterprise. The authors of the article believe that the main task in the enterprise development is to actualize the cost model for the technological equipment of the manufacture and to reduce the costs on manufacturing products. This approach allows us to improve the product quality with a gradual transition to new technological processes. The novelty of the research is the fact that the research is carried out on the example of a technological enterprise of a long production cycle, that allows long-term provide the functioning and development of production, as well as solving the tasks that arise when expanding the assortment and optimization the whole enterprise structure in a whole. The authors of the article conducted a factor analysis and calculation of the effectiveness of the proposed measures. Indicated that should be understood under a structural understanding of increasing the economic structure and the overall efficiency of the enterprise functioning. A promising area of research is the formation of predictive models that will allow predicting the effectiveness of expenses of the company's market position.